Seismic Evaluation and Retrofit of Reinforced Concrete Buildings with Masonry Infills Based on Material Strain Limit Approach - Mangeshkumar R. Shendkar; Denise-Penelope N. Kontoni; Sasankasekhar Mandal; Pabitra Ranjan Maiti; Omid Tavasoli (Shock and Vibration)
The seismic evaluation and retrofit of reinforced concrete (RC) structures considering masonry infills is the correct methodology because the infill walls are an essential part of RC structures and increase the stiffness and strength of structures in seismically active areas. A three-dimensional four-storey building with masonry infills has been analyzed with nonlinear static adaptive pushover analysis by using the SeismoStruct software. Two models have been considered in this study: the first model is a full RC-infilled frame and the second model is an open ground storey RC-infilled frame. The infill walls have been modeled as a double strut nonlinear cyclic model. In this study, the “material strain limit approach” is first time used for the seismic evaluation of RC buildings with masonry infills. This method is based on the threshold strain limit of concrete and steel to identify the actual damage scenarios of the structural members of RC structures. The two models of the four-storey RC building have been retrofitted with local and global strengthening techniques (RC-jacketing method and incorporation of infills) as per the requirements of the structure to evaluate their effect on the response reduction factor (R) because the R-factor is an important design tool that shows the level of inelasticity in a structure. A significant increase in the response reduction factor (R) and structural plan density (SPD) has been observed in the case of the open ground storey RC-infilled frame after the retrofit. Thus, this paper aims to present a most effective way for the seismic evaluation and retrofit of any reinforced concrete structure through the material strain limit approach.